2006
DOI: 10.1590/s1415-43662006000100023
|View full text |Cite
|
Sign up to set email alerts
|

Modelos analíticos do crescimento populacional de Sitophilus zeamais em trigo armazenado

Abstract: RESUMOPara se atingir os objetivos propostos neste trabalho, desenvolveram-se modelos analíticos do crescimento populacional de S. zeamais em grãos de trigo armazenados com teor de umidade de 11,1%. O crescimento populacional foi avaliado durante 90 dias de armazenagem, nas temperaturas de 16, 20, 24, 28, 32 e 36 °C, partindo-se de infestações iniciais que variaram de 1,3 a 9,3 insetos por kg de trigo. Os modelos explicaram de 93,9 a 98,9% da variação na densidade populacional. O crescimento populacional foi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…1b). Similarly, SILVA et al (2006) found that the population growth of S. zeamais in wheat seeds was affected by the population size that initiated infestation, so the greater the initial infestation, the greater the population growth during storage at 28 °C. Also, by the number of seeds infested verified, no seeds with injuries or presence of S. zeamais were observed in the treatment without infestation, indicating that there was no seed attack by this pest before the installation of the experiment (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…1b). Similarly, SILVA et al (2006) found that the population growth of S. zeamais in wheat seeds was affected by the population size that initiated infestation, so the greater the initial infestation, the greater the population growth during storage at 28 °C. Also, by the number of seeds infested verified, no seeds with injuries or presence of S. zeamais were observed in the treatment without infestation, indicating that there was no seed attack by this pest before the installation of the experiment (Fig.…”
Section: Resultsmentioning
confidence: 90%